Substance use and misuse and potential doping behaviour in Rugby Union players - Sekulic, D.; Bjelanovic, L.; Pehar, M.; Pelivan, K.; Zenic, N. (Research in Sports Medicine, 2014)
The aims of this investigation were to compile evidence on substance-use-and-misuse (SUM) and to identify factors related to potential-doping-behaviour (PDB) in rugby union. The subjects were 105 rugby athletes (all males; 23.4 ± 4.1 years; 99% respondents). The variables included socio-demographic factors, SUM-data, sport-factors, knowledge-on-doping (KD), and PDB. Data showed high alcohol consumption, with more than 30% of the athletes binge drinking at least once per week. Approximately 52% of the subjects used dietary-supplementation (DS) and 23% reported PDB, whereas 55% believed that doping is present in rugby. Forward conditional logistic regression revealed that less rugby experience (OR:1.286; 95%CI:1.058-1.563; p < 0.05), less smoking (OR:2.034; 95%CI:1.100-3.760; p < 0.05), higher DS usage (OR:5.543; 95%CI:1.666-18.444; p < 0.01), and a stronger belief that doping is present in rugby (OR:0.305; 95%CI:0.066-0.638; p < 0.01) were significant predictors of PDB. The high PDB and alcohol consumption warrant a serious intervention on these problems in rugby.